Amygdala–prefrontal interactions in (mal)adaptive learning. Issue 3 (March 2015) - Likhtik, Ekaterina; Paz, Rony
Highlights Threat and safety encoding in the amygdala. mPFC-BLA communication promotes better discrimination of stimulus valence. BLA follows mPFC activity during safety and successful stimulus discrimination. Role of oscillations in mPFC-BLA circuit during threat and safety processing.